An Analysis of Factors Affecting English Pronunciation in Students’ Speaking Skills at SMAN 1 Panji - Nuril Firdaus; Iffah, Ukhtul; Agustin, Nurul (CV Kalimasada Group, 2025)
This study aims to identify the factors contributing to pronunciation errors among students of SMAN 1 Panji when speaking English. Data were collected from 37 students through a qualitative descriptive research approach. The instruments used included oral tests and interviews. The findings revealed several challenges encountered by the students at SMAN 1 Panji regarding English pronunciation. These included limited knowledge, a lack of support, and most notably, the strong influence of their mother tongue. Additionally, the lack of regular pronunciation practice in their daily activities made it challenging for students to correctly pronounce many English words.